Citrus Canker and Citrus Leprosis Fruit Symptom Comparison - Amit Levy; Jamie D. Burrow; Megan Dewdney (EDIS)
This publication is intended to guide citrus growers in distinguishing the difference between citrus canker and citrus leprosis.